Determinants of Food Waste Behavior in Culinary Tourism in Batam City: The Role of Intention to Reduce Food Waste, Attitude, and Personal Norm - Alhamdi, Rezki; Saputra, Eryd (Electronic Journal of Education, Social Economics and Technology, 2025)
Culinary tourism not only offers gastronomic experiences but also contributes to the increase of food waste. This food waste arises from tourists’ behavior of not finishing their meals. The purpose of this study is to identify the factors that influence tourists’ food waste behavior, specifically their tendency not to finish their food, which eventually ends up in the trash at culinary tourism sites in Batam City. This research employs a quantitative approach with 325 respondents who have visited culinary tourism destinations in Batam City. The questionnaire used as the research instrument was first validated by culinary industry experts through a Focus Group Discussion (FGD). Data were analyzed using PLS-SEM, including outer model testing to ensure the validity and reliability of the constructs, and inner model testing to examine the relationships among variables. The findings indicate that personal norm has a significant effect on the intention to reduce food waste, whereas attitude and food taste do not. Furthermore, for the mediation effect through food waste behavior, only personal norm shows a significant indirect effect mediated by the intention to reduce food waste, while food taste and attitude show no significant influence. This study calls for greater awareness and concern toward food consumption, emphasizing the importance of finishing meals during culinary tourism activities.